The practices of public spaces in traditional neighborhoods: case of the Argoub district, city of M'sila-Algeria - Hadji, Abdelkader; Feloussia, Lahcene (Journal of Environmental Engineering and Landscape Management, 2025)
Public space seems to have become one of the key elements of local development policies. As such, our study will focus on a traditional neighborhood called Argoub located in the center of the city of M’sila in Algeria, the public spaces of this neighborhood have long been the fundamental structure and the filter of reading of the neighborhood, they have deteriorated and to remedy this problem, the Observation shows that the public space in this district is distorted and its use for heterogeneous purposes than those previously planned, but this diversion of use continues to fragment the public space and reduce it to an obstructed space. The local authorities have carried out limited urban improvement of these spaces to perpetuate and improve their urban quality.This study aims to measure the quality of these spaces, to clarify the notion of traditional public space, and to identify its different practices. For this research, we chose as a methodology recurring observation reinforced by situational observation, while taking into account the urban and historical context of this district. Without permanent control from local authorities, illegal interventions by residents in the spaces in question have completely changed the alleys into stifling spaces used only for transition and not for social interaction.Despite the limited intervention of urban planning services to safeguard the urban fabric network and revive traditional public spaces, the ongoing change practices by residents have had a negative influence on the urban landscape of the neighborhood in general. As such, we will be faced with the following challenges: security, physical and visual quality, and economic attractiveness must, at the end of planning, require a real global reflection on these different urban forms so that their management is coherent and thoughtful. In this regard, the obvious question is: what practical measures should be taken to respond to the problems of landscape and spatial qualities of these spaces and contribute more generally to their sustainability?